Design and Implementation of Web-Based Product Order and Delivery Management Information System at Dheafin Bakery - Wahyuni, Risna; Tifani, Putri; Febiola Simanungkalit, Imelda; Najiyah Yulhan, Zahra; Ain Fauziah, Tria; Hidayati, Nani (Devitara Innovations, 2025)
This study aims to design and implement a web-based order and delivery management information system for Dheafin Bakery, a small and medium enterprise. The system was developed as a solution to operational problems that have been carried out manually, such as order recording, customer and product data management, and the delivery process. A software engineering approach was used in the development of this system, with the Waterfall method which includes the stages of needs analysis, design, implementation, testing, and maintenance. The system was built using the PHP programming language and MySQL database, and was designed responsively so that it can be accessed through various devices. The implementation results show that the system is able to integrate the ordering and delivery process automatically and in real-time, reduce recording errors, speed up the workflow, and increase efficiency and customer satisfaction. The system also provides easy-to-use customer, product, and order tracking management features. Thus, this information system has succeeded in significantly improving Dheafin Bakery's operational performance and has the potential to become a model for similar applications for other small and medium enterprises.